Management by Wandering Around (MBWA) as a leadership mechanism in UiTM Pahang / Hasnizawati Hashim and Rozieana A. Halid @ Khalid - Hashim, Hasnizawati; A. Halid @ Khalid, Rozieana (2008)
Relatively modest coordination among employees could be met through various basic management principles. Management By Wandering Around (MBWA) is one of the mechanisms that can be applied towards a better working environment in UiTM Pahang. Probably, it could help in gaining more productivity interest and harmonious relationship among employees and the higher level of management as MBWA required managers to be closed with one another. It could give lots of opportunities in revealing problems that are not implied directly or known to manager. This concept paper will discuss the application of MBWA in UiTM Pahang and the benefits gained as well. Few examples of companies that have successfully applied this concept will be explained in detail to support the statement of the effectiveness of MBWA.